Carthage : A Biography - Hoyos, Dexter (Cities of the Ancient World Ser, 2017)
Cover -- Half Title -- Series Page -- Title page -- Copyright page -- Contents -- List of illustrations -- Maps -- Acknowledgements -- 1. Dido's city -- Foundation -- The early city -- Society and state -- 2. Trade and the beginnings of empire -- Trade, wealth, and growth -- Commercial expansion and territorial hegemony -- Two famous Atlantic enterprises -- 3. City life and religion -- Religion at Carthage -- Child sacrifice? -- The cityscape -- The enclosed harbours -- 4. Society and government -- Names -- Art and literature -- Aristocrats and military families -- Population and people -- Government -- Carthage's fleets -- Carthage's armies -- 5. Politics, politicians, and Carthage in Libya -- Sixth-century bc politics: Malchus -- The Magonid family dynasty -- Politics in the fourth century: the first Hanno 'the Great' -- Later fourth-century politics: Mago, Gisco, and after -- Third-century stresses -- The era of the Barcids -- Reform and disaster -- 6. Carthage versus the Greeks -- The fifth-century Sicilian wars -- Carthage versus Dionysius -- Disaster at the river Crimisus -- The trauma of Agathocles -- Carthage's last Greek war -- 7. Fighting Rome -- Carthage and Rome before 264 bc -- Messana, Syracuse, and Acragas -- Carthage's longest war -- The Truceless War -- The Barcids, Spain, and Rome -- The Second Punic War: Hannibal's offensive -- The war's middle years -- The Metaurus and Zama -- 8. The death of Punic Carthage -- Peace and Masinissa -- The Third Punic War begins -- Carthage besieged -- Scipio Aemilianus takes command -- The fall of Carthage -- Aftermath -- Why was Carthage destroyed? -- 9. Colonia Iulia Concordia Carthago -- The road to recolonisation -- The refoundation of Carthage -- Proconsuls, government, and taxes -- The major public structures -- Culture and wealth -- Imperial politics and impacts.